2014
DOI: 10.1126/science.1253119
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight controls water column processing of carbon in arctic fresh waters

Abstract: Carbon in thawing permafrost soils may have global impacts on climate change; however, the factors that control its processing and fate are poorly understood. The dominant fate of dissolved organic carbon (DOC) released from soils to inland waters is either complete oxidation to CO2 or partial oxidation and river export to oceans. Although both processes are most often attributed to bacterial respiration, we found that photochemical oxidation exceeds rates of respiration and accounts for 70 to 95% of total DOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
648
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(719 citation statements)
references
References 52 publications
32
648
10
Order By: Relevance
“…Our results supported our initial hypothesis that freshet DOM bioavailability would continually increase throughout the irradiation incubation, and were consistent with prior observations of photodegradation in a range of riverine (e.g., Opsahl and Benner 1998;Moran et al 1999;Spencer et al 2009) and other freshwater (e.g., Bertilsson and Tranvik 2000;Osburn et al 2001;Cory et al 2014) environments.…”
Section: Photoreactivity Of Mackenzie River Freshet Domsupporting
confidence: 80%
See 2 more Smart Citations
“…Our results supported our initial hypothesis that freshet DOM bioavailability would continually increase throughout the irradiation incubation, and were consistent with prior observations of photodegradation in a range of riverine (e.g., Opsahl and Benner 1998;Moran et al 1999;Spencer et al 2009) and other freshwater (e.g., Bertilsson and Tranvik 2000;Osburn et al 2001;Cory et al 2014) environments.…”
Section: Photoreactivity Of Mackenzie River Freshet Domsupporting
confidence: 80%
“…8b), where an initial sharp increase in SBP also suggested that the surviving bacteria were released from a relative shortage of growth substrate. Increased BP and growth have been observed in the presence of irradiated DOM in many freshwater systems (e.g., Anesio et al 2005;Paul et al 2012), including in the circumpolar Arctic (Cory et al 2013;Ward et al 2017), where photochemical oxidation of DOM accounts for the majority of C processing (Cory et al 2014). Prior work in the Mackenzie Delta has shown that lower molecular weight DOM derived from macrophytes supports higher rates of BGE in communities isolated from a variety of habitats (including TK and CON lakes;Tank 2009).…”
Section: Photoreactivity Of Mackenzie River Freshet Dommentioning
confidence: 99%
See 1 more Smart Citation
“…Similar seasonal transformations of DOM NMR resonances have been observed in other lake environments and attributed to microbial degradation 53 . However, photo-oxidation can also be an important pathway of terrestrial DOM removal and modification in some lakes 54 , and in this context it is important to note that UAL in particular, and FLL are periodically ice covered, whereas LT is not, and thus the exposure time of DOM to ultraviolet also differs between these lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Once in the drainage network, it is susceptible to photochemical breakdown (e.g. Köhler et al, 2002;Cory et al, 2014) and may also be utilised as an energy and carbon source by heterotrophic organisms (e.g. Battin et al, 2008).…”
Section: 'On-site' and 'Off-site' Emissionsmentioning
confidence: 99%